Instruments of darkness - Robertson, Imogen, 1973- (Pamela Dorman Books/Viking, 2011)
Discovering a dead neighbor from a menacing local estate, the unconventional Mrs. Westerman of 1780 Sussex enlists a reclusive local anatomist to uncover the family's secrets, which include ties to the American Revolution and links to the murder of a music shop owner.